Presence of microplastics in two common dried marine fish species from Bangladesh - Hasan, Jabed; Islam, S.M. Majharul; Alam, Md Samsul; Johnson, Derek; Belton, Ben; Hossain, Mostafa Ali Reza; Shahjahan, Md (Marine pollution bulletin, 2022)
We examined microplastics (MP) in two commercially important dried fish, Bombay duck (Harpadon nehereus) and ribbon fish (Trichiurus lepturus), collected from two sites on the Bay of Bengal (Cox's Bazar and Kuakata). The number of MP found in dried Bombay duck and ribbon fish from Kuakata was significantly higher (41.33 g−1 and 46.00 g−1, respectively) than the MP present in samples collected from Cox's Bazar (28.54 g−1 and 34.17 g−1, respectively). Fibers were the most common type of MP identified in all samples (41–64%), followed by fragments (22–34%), microbeads (9–16%), films (3–4%), foams (1–4%), and pellets (0–2%). ATR-FTIR analysis revealed three different types of MP polymer - polyethylene (35–45%), polystyrene (20–30%) and polyamide (30–45%) in the dried fish samples. The study confirms the presence of high MP loads in dried fish from the Bay of Bengal, with high potential of trophic transfer of MP to the human body. •Microplastics (MP) were identified in the two most common marine dried fish products in Bangladesh.•High levels of MP were found in all samples of both fish species from two locations.•Fibers were the most common type of MP identified.•ATR-FTIR analysis of dried fish samples revealed polymer types of polyethylene, polystyrene and polyamide.•MP in dried fish may be transferred to the human body through consumption, with unknown health effects.